Yield and production cost of Chlorella sp. culture in a Fibonacci-type photobioreactor. (June 2023) - Díaz, Juan Pablo; Inostroza, Cristian; Acién, F. Gabriel
Abstract: In this research work, the performance of a Fibonacci-type photobioreactor scaled to 2500L to produce Chlorella sp. . is presented. The results show that this photobioreactor design kept the Chlorella culture at its optimal temperature, pH and dissolved oxygen levels. Despite the fact of being a closed reactor, the temperature was kept below 30 °C while the dissolved oxygen was maintained below 200 % Sat. under outdoor conditions at which the mean daily solar radiation ranged from 139 to 450 µE/m 2 s. Under these conditions, a maximum specific growth rate of 0.31 day −1, a biomass concentration of 1.9 g/L, and volumetric biomass productivity of 0.37 g/L day were achieved. The Fibonacci-type tubular photobioreactor presented here offers substantial advances compared to classic tubular photobioreactors, as it has proven to be flexible in its geometric design and it can adapt its parameters to the photosynthetic needs of the microalgae to ensure maximum efficiency, thus making it an alternative to conventional tubular systems. In addition, it is feasible to consider industrial production, since its costs have been estimated as 27.4 €/kg, at an annual production scale of 37 tons. Graphical Abstract: Fibonacci-type photobioreactor. ga1 Highlights: The performance of Fibonacci-type photobioreactors was demonstrated at a 2500L scale. Fibonacci-type photobioreactors allow dissolved oxygen below 200 %Sat while controlling pH and temperature. The V/S ratio is the key factor to scale-up Fibonacci-type photobioreactors. The proposed technology allows producing high-quality biomass at a moderate cost.